Implementasi Kebijakan Moderasi Beragama Pada Perguruan Tinggi Keagamaan Islam Negeri (PTKIN) Aceh - Maizuddin, Maizuddin; Sumardi, Dedy; Zulihafnani, Zulihafnani (Universitas Islam Negeri Raden Intan Lampung, 2023)
This article describes the implementation of religious moderation at the State Islamic Religious University (Perguruan Tinggi Keagamaan Islam Negeri/PTKIN) Aceh. Religious moderation has become a strong discourse and policy in the Ministry of Religion, including PTKIN as part of the Ministry of Religion. This article attempts to describe two aspects of religious moderation. The first, describes the formulation of the religious moderation policy at PTKIN Aceh. Second, discusses the implementation of the religious moderation policy. The research was conducted in four locations, namely: UIN Ar-Raniry, IAIN Lhokseumawe, IAIN Takengon, and STAIN Meulaboh with a descriptive qualitative approach. The results showed that the formulation of a religious moderation policy had the power of having been well prepared, but there was still a long time span between one policy and the next so that PTKIN experienced problems in its implementation. The implementation budget is charged to each institution. Second, the implementation of the policy of religious moderation has begun at PTKIN Aceh. In general, the Religious Moderation House has been established even though it is late and has not been active due to various obstacles. However, the socialization of the narrative has been running even though it is not carried out by the Religious Moderation House. Seminars, workshops, public lectures, and scheduled study forums are forms of socializing the narrative of religious moderation. The obstacles faced are more related to the financing of activities that are increasingly difficult due to the refocusing of the budget that has been in several stages.